Care of the Critically Ill Emergency Department Patient with Acute Kidney Injury. (24th November 2011) - Joslin, Jennifer; Ostermann, Marlies
Abstract : Introduction. Acute Kidney Injury (AKI) is common and associated with significant mortality and complications. Exact data on the epidemiology of AKI in the Emergency Department (ED) are sparse. This review aims to summarise the key principles for managing AKI patients in the ED. Principal Findings . Timely resuscitation, goal-directed correction of fluid depletion and hypotension, and appropriate management of the underlying illness are essential in preventing or limiting AKI. There is no specific curative therapy for AKI. Key principles of secondary prevention are identification of patients with early AKI, discontinuation of nephrotoxic medication where possible, attention to fluid resuscitation, and awareness of the risks of contrast-induced nephropathy. In patients with advanced AKI, arrangements for renal replacement therapy need to be made before the onset of life-threatening uraemic complications. Conclusions . Research and guidelines regarding AKI in the ED are lacking and AKI practice from critical care departments should be adopted.